The Importance of Fundraising for Sustainability of Nonprofit Organizations - Dadić, Lorena (Oeconomica Jadertina, 2017)
Non-profit organizations represent the basis for all democratic societies. They have a key role in modernizing welfare states, building trust, civic virtues and social capital. Cooperation within the local community creates additional capabilities (capacities) for problem solving and improvement of the quality of life. However there are a number of managerial issues relating to the activities of the non-profit organizations. The most common problems are the lack of financial resources and the unsustainability of development, the lack of work professionalism, lack of transparency of organizations and the connection to a broader membership, lack of leadership, poor networking and a low level of cooperation between organizations, low level of cooperation with the media and an underdeveloped role of advocacy (Bežovan, 2005). The lack of financial resources is one of the main problems nowadays, primarily due to non-profit organizations high dependency on the public budget (grants). Simultaneously, there is an increasing number of registered non-profit organizations that compete for a continuously decreasing number of public grants. Therefore, long-term sustainability of non-profit organizations is highly questionable. The solution can be found in carefully planned fundraising activities involving potential donors or sponsors in order to increase the proportion of grants and self-earned revenues and therefore reducing the need for public grants. Fundraising is still relatively unknown within the Croatian non-profit sector, which is also confirmed by studies indicating that non-profit organizations in Croatia are not familiar with what the term “fundraising” comprises.
Keywords: non-profit organizations; sustainability of non-profit organizations; fundraising; donations; sponsorships